Measurement of Coordinated Development Level of Cross-Regional Urban Agglomerations from the Perspective of Industrial Transformation and Upgrading - Wu, Yiming (Transactions on Social Science, Education and Humanities Research, 2023)
Based on the panel data of Beijing-Tianjin-Hebei, Yangtze River Delta and Pearl River Delta city agglomerations in China from 2014 to 2020, this paper uses dynamic models to measure the coordinated economic development level of cross-regional urban agglomerations from the perspective of industrial transformation and upgrading, and estimates and analyzes relevant variables. The results show that the coordinated economic development degree of the Yangtze River Delta urban agglomeration, the Beijing-Tianjin-Hebei urban agglomeration and the Pearl River Delta urban agglomeration shows a fluctuating upward trend, but there are differences within and between urban agglomerations. There is a significant lagging effect of industrial transformation and upgrading on the coordinated development of cross-regional economy. The driving capacity of tertiary industry plays a role in promoting the impact of industrial transformation and upgrading on the coordinated economic development of cross-regional urban agglomerations, and the effect is stronger than the direct role of industrial transformation and upgrading.